Strategies for successful personal branding of celebrities on social media platforms: Involvement or information sharing? - Lo, Fang‐Yi; Peng, Jing‐Xiang (Psychology & marketing, 2022)
This study explores Internet celebrities’ personal brand development motivations and their strategies for successful personal branding practices. It divides the motivations of Internet celebrities to build their personal brands into internal and external factors as a basic framework to explore the establishment of a personal brand. We collect empirical data on 280 Internet celebrities from Taiwan through online and paper‐based questionnaires and conduct structure equation modeling to examine any causal relationships. Statistical results support the main hypothesis that both internal and external motivations push them to adopt involvement and information sharing as their main activities when building a personal brand. However, only involvement is able to create a successful personal brand, as information sharing alone fails to demonstrate the expected effects. We employ the mixed‐method approach to collect data through qualitative and quantitative sources. In‐depth qualitative interviews of successful Internet celebrities also corroborate the empirical results. This study suggests that future Internet celebrities should focus on involvement activities, rather than just sharing information, if they want to create a successful personal brand.